Upaya Meningkatkan Hasil Belajar Ekonomi dengan Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) - Iin Nurbudiyani; Yean's Virgi Handhayanie (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
This study aims to find out: (1) learning activities of students in economic learning using a type of cooperative learning model Two Stay Two Stray, (2) knowing the improvement of students' financial learning outcomes after using the Two Stay Two Stray type learning model. Subject in this study was the X grade social studies at the Madrasah Aliyah Miftahul Jannah Palangka Raya as many as 20 students. The method used by researchers is using the Class Action Research (CAR) design. Based on the results of the study It was concluded that: (1) learning activities of students of class X IPS in Islamic Senior High School Miftahul Jannah Palangka Raya are more active during economic learning using the Two Stay Two Stray type cooperative learning model. (2) Learning outcomes students experience improvement, in the first cycle completeness classically reaches 55% (11 people) of students complete. In cycle II the percentage of learning outcomes increases namely completeness in classics reaches 95% (19 people) students who complete